Relationship between hematocrit levels and intraocular pressure in men and women: A population-based cross-sectional study. Issue 41 (October 2017) - Cohen, Eytan; Kramer, Michal; Shochat, Tzippy; Goldberg, Elad; Krause, Ilan
Abstract : Abstract: To assess a possible relationship between hematocrit level and intraocular pressure (IOP) in both men and women. Data were collected from medical records of individuals examined at a screening center in Israel between the years 2000 and 2013. Hematocrit levels were categorized as low, normal, and high and by sex; IOP values were categorized as < 18 mmHg and ≥18 mmHg. Cross-sectional analysis was performed on 18, 424 subjects of mean (standard deviation) age 46 (10) years (68% male). Normal-range hematocrit for men was 42% to 52% and 37% to 47% for women. In men, mean [95% confidence interval CI)] IOP values by hematocrit level were as follows: below-normal hematocrit, 13.3 mmHg (13.2–13.3), normal hematocrit, 13.5 mmHg (13.4–13.5), above-normal hematocrit, 14.3 mmHg (13.5–15.2) ( P  < .001). Corresponding values in women were 12.9 mmHg (12.8–13.0), 13.0 mmHg (13.0–13.1), and 14.2 mmHg (12.9–15.6) ( P  = .014). The difference remained significant for men ( P  < .001) after adjustment for age, hypertension, diabetes, and body mass index. Men (but not women) with a low hematocrit were found to have a significantly lower odds ratio (95% CI) of having IOP ≥18 mmHg than men with normal hematocrit: nonadjusted model, 0.761 (0.631–0.919); adjusted model, 0.771 (0.638–0.932) ( P  < .01). It is possible that a raised hematocrit level may also contribute to an elevated IOP in men in addition to the classic risk factors.